The efficiency of monetary policy during the zero lower bound period - Mandok, Denis (2016)
This thesis explores efficiency of monetary policy under zero lower bound condition. At first, is defined a role of monetary policy and criteria to judge the effectiveness of monetary policy are introduced. Then reactions of central banks of USA, Japan and Euro zone are explored. Thesis found out that monetary policy can be effective under a condition of zero lower bound. As last is introduced idea how to improve current monetary regime.